Analisis Pengaruh Pengeluaran Pemerintah Bidang Infrastruktur, Pendidikan Kesehatan terhadap Pertumbuhan Ekonomi di Kabupaten Kutai Kartanegara - Dedi Setiadi; Aji Sofyan Effendi; Juliansyah Roy (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2017)
The purpose of this research is to analyze the effect of government spending infrastructure sector   of   eduation, healt   and   the   economic   growth   in   Kutai Kartanegara years 2005-2014.  Government spending infrastructure sector represented by government spending variable road sector, the government sector education infrastructure spending, government spending and the healt sector is basically an investment to economic growth. Effect on development of these sector cannot have a direct impact but require a period to be able to feel the impact. There is a time lag when the government issued a construction budget or statespending for these three sector with the impact of the policy. The we need a study using time series is long enough. Research using time series will help see the effect of government spending on these sector to economic growth. Government investment in education, healt and infrastructure will lead to improved quality of human capital and physical infrastructure, this will also spur economic investment.  Economic investment to futher   affect   economic   growth, because   of   the   large   capital   available   for development. The analysis model is the Error Correction Model (ECM), this model is expected to explain the behavior of short-term and long-term. In addition, this model is able to find solutions to the problem of time series variables are not stasionary in econometrics.Keywords: Economic growth government spending